Development Of A Multilingual System To Improved Automated Teller Machine Functionalities In Uganda - Stephen Gbenga Fashoto; Gabriel Ogunleye; Patrick Okullu; Akeem Shonubi; Petros Mashwama (Politeknik Negeri Padang, 2017)
This paper presented a new multilingual language for Automated Teller Machine (ATM) in Uganda which serves as an extension to the existing Languages. The existing ATMs have only English, Kiswahili and Luganda as the only available languages. Hence, findings revealed that there are still some prevalent languages e.g. Ateso language that are widely spoken among the people of Uganda which the present ATMs in the country have not captured. The objective of this paper was to propose the integration of the new language (Ateso language) to the existing languages. In this paper, a new language was adopted when it was realized that some people especially in the Buganda region could not manage to interact with the ATMs because they were illiterate. The developed multilingual system prototype was tested using some empirical data and was found to successfully imitate ATM transactions in the local Uganda languages. The results of the study supported the positive impacts on customers that reside in the rural areas since its improved interaction of more users on the ATMs. This paper demonstrated the use of Ateso language for different transactions on the ATM system. The implementation by the banking institutions can aid the ATM users to make more flexible decisions on the usage of the ATM machines.